Knowledge of caregivers of a pediatric inpatient unit about urinary tract infection (Research, Society and Development, 2021)
Objective: To describe and assess the knowledge of caregivers at a pediatric inpatient unit about urinary tract infection. Methods: Cross-sectional, descriptive, quantitative, analytical study with correlation between variables, with 109 companions in inpatient units of a pediatric hospital. An instrument was used to collect sociodemographic data, a questionnaire to verify knowledge about Urinary Tract Infection and, at the end, educational material was delivered. Results: The average age of companions was 33 years; 94.5% female, 34.86% did not complete high school, 48.63% drank less than two liters of water/day and 70.64% of them already had urinary tract infection. With regard to children, the average age was five years; 53% were female, 15.1% were hospitalized for urinary tract infection and 37.61% had already had the infection, 56.88% drank less than a liter of water/day and 55.96% wore diapers. In a question that mentioned that proper hygiene habits interfere in preventing this infection, 45% of the companions got the answer wrong. Conclusion: There was a reasonable knowledge of the companions. The correct orientation of these people is essential for the prevention of urinary tract infection and the availability of educational material provided greater awareness on the subject.